PENGARUH LATIHAN DUMBLE HIGH SWING DAN MEDICINE BALL TERHADAP KEMAMPUAN SMASH DALAM PERMAINAN BULUTANGKIS PADA CLUB WARNA AGUNG MATARAM TAHUN 2016 - Soemardiawan, Soemardiawan (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2017)
In playing badminton students still lack the ability to smash. Is There Effect Of Dumble High Swing And Medicine Ball Exercises On The Smash Ability In Badminton Game At The Mataram Grand Color Club In 2016, so based on these problems this study aims to find out the Effect of Dumble High Swing Exercise and Medicine Ball on Smash Ability in Badminton Game On Club Warna Agung Mataram Year 2016. The research design used is One Group Pretest-Postest Design with the studied population of 16 players, then in this study the researchers will take the entire population into a sample (population study). To obtain the data in this research, the action test method is used as the principal method while the documentation method as the auxiliary method. The analysis of statistical data with t-test formula with the research design used is t-test of similar samples (dependent sample) with a sample of 16 students. The results of the analysis for the Dumble High Swing group were obtained at 1,490 <t-tables of 2,365 and for the Medicine Ball group obtained t-count of 6,071> t-table of 2,365, with degrees of freedom (df) N-1 = 7. Based on the data analysis to answer the proposed research hypothesis, obtained value "t" count of 4.198 with 5% significant level and N-1 = 15 obtained "t" table that is 2.131. Thus t count is greater than t table which means it can be concluded There is Effect of Dumble High Swing Exercise and Medicine Ball Against Smash Ability In Badminton Game At Club Warna Agung Mataram Year 2016Â 